Booth reservation system (BRSYS) / Nazira Wati Ibrahim - Ibrahim, Nazira Wati (2014)
Web-based system is programs that run on web servers and uses web pages as the user interface. Nowadays, peoples gained a lot of benefits from the application usage of Internet website and online reservation system. Currently, die application is dominating the modem information technology. So, the project entitled “BRSYS” web-based system was developed to ease student and staff in making booth reservation process and administrator to manage booth reservation of event held in UiTM (Terengganu). This project was developed using RAD techniques which are requirement, analysis, design and development phases that can do the backward process. Reservation systems of BRSYS were enable the student and staffto register their account, update their profile, upload file and make booth reservation. Besides that, the administrator will control all the processes which are add, update, search and delete information. Therefore, he or she also can approve status of booth reservation. The evaluation techniques that had been used in complete the project were interview and distribute questionnaires to student and staff in UiTM (Terengganu). Overall from the results, construct of usability and accessibility which are user agree that they were fully understood all instructions provided in using the system have shown with highest (Mean = 4.303 and SD = 0.5294). This project also will create paperless usage and save time for student and staff to make reservation. The BRSYS web-based system could be improved in future by other researcher in term of user interface as well as its functionality.